Full Characterization of Quantum Optical Detectors - Coldenstrodt-Ronge, H; Worsley, A; Lundeen, J; Feito, A; Pregnell, K; Silberhorn, C; Mosley, P; Smith, B; Puentes, G; Thomas-Peter, N; Ralph, T; Eisert, J; et al. (2009)
Full characterization of detectors in the quantum regime is presented. We determine the POVM elements of a photon-number-resolving detector. A method for precise calibration of detector efficiency is demonstrated. © 2009 IEEE.